Propriedades físico-mecânicas e carbono do solo após aplicações sucessivas de resíduos orgânicos de aves e suínos - Freitas, José Alcides Soares de (2018)
The fertilization of agricultural crops with organic residues from swine and poultry farming is a widespread practice among Brazilian farmers and results in productivity gains mainly due to the content of nutrients present in these materials. On the other hand, the continued addition of organic residues can result in changes in the physical properties and mechanical behavior of the soil, increasing or reducing its quality and influencing the growth and development of agricultural crops. In this sense, this study aimed to investigate the influence of high dose applications of pig slurry and poultry litter over four years on the physical, mechanical properties and organic carbon of a very clayey Red Latosol of the Upper Middle Uruguay, in Rio Grande do Sul. For this, an experiment was carried out in a randomized complete block design with four replicates and treatments: 1- Control (T1): without application of pig slurry (DLS) or poultry litter (CA); 2- DLS160: Surface application of 160 m³ ha-1 year-1 of DLS; 3- DLS320: Surface application of 320 m³ ha-1 year-1 of DLS; 4- DLS480: Surface application of 480 m³ ha-1 year-1 of DLS; 5- CA6: Surface application of 6 Mg ha-1 year-1 of CA; 6- CA12: Surface application of 12 Mg ha-1 year-1 of CA e; 7- CA18: Surface application of 18 Mg ha-1 year-1 of CA. In all treatments, the annual dose was divided into four applications, being made one in each season of the year. Deformed and undeformed soil samples were collected in the layers of 0.00 - 0.05 m, 0.05 - 0.10 m and 0.10 - 0.20 m, in which the following variables were evaluated: organic carbon content, soil density, maximum density, relative density, total porosity, macroporosity, microporosity, mechanical resistance to penetration, preconsolidation pressure, compression index, stability of aggregates in water, clay dispersed in water, flocculation degree and infiltration of water in the soil. The DLS and CA applications increased the soil organic carbon content, but no significant differences were observed between the two residues used. In the 0.00 to 0.05 m layer, soil density was reduced while total porosity and macroporosity were increased as a function of DLS and CA additions. No significant changes were observed in the mechanical resistance to penetration and soil preconsolidation pressure. DMG and DMP from the soil aggregates were not affected by the additions of the organic residues, and the clay content dispersed in water decreased with increasing organic carbon contents, while the degree of flocculation increased. No significant effects on soil water infiltration rate were observed.